Projeto e implantação de usina solar fotovoltaica com módulos de tecnologia bifacial - Medeiros Filho, Ricardo Machado de (2021)
Currently, with the exponential growth that the photovoltaic solar energy market has been having in the country, the introduction of new technologies in the sector is motivated by the search for lower costs associated with the implementation of these generation systems and by the optimization of electricity production. Within this context, bifacial photovoltaic modules emerge as an alternative to be studied for this purpose. The main objective of this work is to present a technology of bifacial photovoltaic components and address the main factors that must be taken into account when dimensioning a photovoltaic solar plant with this type of technology. In addition, the main characteristics that affect the performance of bifacial devices in relation to the gain promoted in the production of electrical energy are evaluated, with an emphasis on the parameters that can be calculated in order to predict the performance of technology compared to technology conventional monofacial modules. Furthermore, the photovoltaic solar plant in question is dimensioned according to the energy demand of a real consumer unit and the system is simulated in a software specialized in photovoltaic studies in order to validate its dimensioning. According to the forecast energy demand, the solar plant needs to be equipped with 222 bifacial type modules with a front face power of 410 Wp each, totaling a photovoltaic solar plant of 91.02 kWp, annual energy production will be around 158 MWh.